PREDIKSI FINANCIAL DISTRESS BERDASARKAN ANALISIS Z-SCORE PADA PERUSAHAAN TEKSTIL DAN GARMENT - Firdausia, Yuli Kurnia; Andikasari, Erlyana (Universitas PGRI Adi Buana, 2017)
The purpose of this research is to find out the financial distress based on the analysis result by using Z-score at garment and textile company which is listed in Indonesia Stock Exchange. The research type is using qualitative descriptive research. The population in this research is garment and textile Company which is listed in Indonesia Stock Exchange for 5 years period which are in the year 2009 until 2013, the sample selection is using purposive sampling and the numbers of samples in this research are 14 garment and textile companies. The data analysis technique is using qualitative descriptive method which are collecting, processing, and interpreting the data obtained theoretically. Based on the research result and the discussion by using Altman Z Score method at the pulp and paper company can be found that the financial condition of each company can be explained as follows: The company which has not indicated value of Z > 2.99 are: PT Pan Brothers Tbk and PT Ricky Putra, it can be said that those two garment and textile companies are in good condition; (2) The companies which have value of Z 1.20-2.99 are PT Panasia Tbk, PT Polychem Tbk, PT Sunson Tbk, PT Indo Rama Tbk, and PT Ever Tbk as a result that all six companies can be categorized in the warning category; (3) The companies which have value of Z < 1.20 are PT Agro Pantes Tbk, PT Unitex Tbk, PT Nusantara Inti Tbk, PT Century Tbk, PT Asia Pasific Tbk, PT Eratex Djaja Tbk, and PT Apac Citra Tbk, both seven companies can be included financial distress. Keywords: financial report, z-score and financial distress